Scope, content and quality of clinical pharmacy practice guidelines: a systematic review - OKUYAN, BETÜL (My University, 2023)
Background: Guidelines for pharmacy practitioners regarding various clinical pharmacy activities have been published in a number of countries. There is a need to review the guidelines and identify the scope of activities covered as a prelude to developing internationally acceptable common guidelines. Aim: To review the scope of clinical pharmacy guidelines and assess the extent to which these guidelines conform to quality standards as per the AGREE II instrument. Method: Medline, Embase, Guideline Central, International Pharmaceutical Abstracts, Google Scholar and Google (for grey literature) were searched for the period 2010 to January 2023. Guidelines which focused on any health care setting and any clinical pharmacy activity were included. Data were extracted and quality assessed independently by two reviewers using the English version of the AGREE II instrument. Results: Thirty-eight guidelines were included, mostly originating from Australia (n = 10), Ireland (n = 8), UK (n = 7) and USA (n = 5). Areas covered included medication reconciliation, medicines optimisation, medication management and transition of care. As per the AGREE II assessment, the highest score was obtained for the scope and purpose domain and the lowest score for rigour of development, mainly due to non-consideration of literature/evidence to inform guideline development. Conclusion: Clinical pharmacy guidelines development processes need to focus on all quality domains and should take a systematic approach to guideline development. Guidelines need to further emphasise person-centred care and clinical communication. There is a scope to harmonise the guidelines internationally considering the diverse practices, standards and legislations across different geographies.
Keywords: Tıp; Temel Eczacılık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; TROPİKAL TIP; FARMAKOLOJİ VE ECZACILIK; TOKSİKOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; TROPICAL MEDICINE; PHARMACOLOGY & PHARMACY; TOXICOLOGY; Toksikoloji; Farmakoloji; Farmasötik bilim; Farmakoloji (tıbbi); Pharmacy; Toxicology; Pharmacology; Pharmaceutical Science; Pharmacology (medical); Clinical pharmacy; Medication review; Medicines optimisation; Practice guidelines